An investigation of mathematical problem posing skills of gifted students - Erdogan, Fatma; Gul, Neslihan (Pegem Akad Yayincilik Egitim Danismanlik Hizmetleri Tic Ltd Sti, 2020)
This study aimed to investigate the mathematical problem posing skills of gifted students. The participants of the study, designed as a case study, were 55 middle school students (20 sixth grade, 17 seventh grade, 18 eighth grade) who were studying at Science and Art Center in a city in the Eastern Anatolia region. Data were collected through a problem posing form which includes a semi-structured problem posing task in which the students were asked to make up three problems (easy, moderately difficult, and difficult) about three different figures given. The students' responses to the problem posing task were analyzed with descriptive analysis method. Results showed that almost all of the problems posed by students were mathematical problems. Seventh and eighth-grade students posed more non-mathematical problems than sixth-grade students. Results also revealed that the students mostly posed extensive problems (related to further steps beyond the three given figures) in easy, moderately difficult and difficult tasks. Problem posing rates of the students with the level of difficulty that progresses hierarchically as desired were found to be quite low in the progression analysis of problems' difficulty level.
Keywords: Mathematical problem posing; Giftedness; Mathematical giftedness; Mathematics education